United States' strategy in the Horn of Africa, 1977-1981 : American political actors roles in a context of regional and international crisis - (:unkn) unknown (My University, 2023)
Descriptions and analysis of a showdown of actors that determined US policy in the Horn of Africa (Ethiopia, Somalia, Djibouti) between 1977 and 1981, during James E. Carter administration. Over a period amid a context of cold war, Djibouti became independant from France, Somalia waged a territorial war against Ethiopia and regional alliances with East and West exacerbated competition between the United States and the USSR. In light of archives and other French and American primary sources, this phd thesis aims to demonstrate how the decision-making process and American diplomacy are influenced within the framework of an African policy in the second part of the 1970s.
Keywords: African Research